Analysis of Good Practices in the Coffee Milling Process: Study Experience in the Municipality of Viotá (Cundinamarca, Colombia) - Giraldo Quintero, Juan José; Niño Mendez, Carlos David; Vianchá Sánchez, Zulma (Ingeniería Solidaria, 2017)
Introduction: The article results from the research Analysis of good practices in the coffee milling process: Study experience in the municipality of Viotá, conducted during 2016 at the Fundación Universitaria Agraria de Colombia (Uniagraria). This research is part of the Viotá Center for Research, Social Innovation and Technological Transfer (ciistt), and is the result of the call Young Researchers and Innovators, under the sena-Colciencias partnership.Method: The coffee milling process in producing farms of the municipality of Viotá was characterized by a checklist, which was structured according to the pepsu and 5m methodology. This consists, on the one hand, in analyzing suppliers, inputs, processes, outputs and users; and on the other, machinery and facilities, methods, labor, raw material and environment.Results: The present conditions of the coffee milling process were established, characterizing the stages of receiving, pulping, pulp handling, mucilage removal, washing and sorting, drying, bagging, storage and transportation.Conclusions: In order to improve coffee processing, it is necessary to consider the availability and functionality of machinery and infrastructure, the skills of employees, the good condition of coffee cherry from the crop, standardization and process control, as well as to ensure the minimum impact on the environment.
Keywords: coffee; practices; process; technology; transformation